Direct and converse theorems for King operators - Finta Zoltán (Acta Universitatis Sapientiae: Mathematica, 2020)
For the sequence of King operators, we establish a direct approximation theorem via the first order Ditzian-Totik modulus of smoothness, and a converse approximation theorem of Berens-Lorentz-type.